Value of information from vibration-based structural health monitoring extracted via Bayesian model updating. (1st March 2022) - Kamariotis, Antonios; Chatzi, Eleni; Straub, Daniel
Abstract: Quantifying the value of the information extracted from a structural health monitoring (SHM) system is an important step towards convincing decision makers to implement these systems. We quantify this value by adaptation of the Bayesian decision analysis framework. In contrast to previous works, we model in detail the entire process of data generation to processing, model updating and reliability calculation, and investigate it on a deteriorating bridge system. The framework assumes that dynamic response data are obtained in a sequential fashion from deployed accelerometers, subsequently processed by an output-only operational modal analysis scheme for identifying the system's modal characteristics. We employ a classical Bayesian model updating methodology to sequentially learn the deterioration and estimate the structural damage evolution over time. This leads to sequential updating of the structural reliability, which constitutes the basis for a preposterior Bayesian decision analysis. Alternative actions are defined and a heuristic-based approach is employed for the life-cycle optimization. By solving the preposterior Bayesian decision analysis, one is able to quantify the benefit of the availability of long-term SHM vibrational data. Numerical investigations show that this framework can provide quantitative measures on the optimality of an SHM system in a specific decision context. Highlights: Quantification of the Value of Information from long-term vibration-based SHM. Adaptation of the Bayesian decision analysis framework. Heuristic-based solution of the life-cycle optimization. Quantitative measures on the optimality of SHM systems in specific decision contexts.